Maternal and perinatal outcome in severe preeclampsia and eclampsia - Saxena, Neha; Bava, Amarjeet Kaur; Nandanwar, Yogeshwar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pre-eclampsia accounts for the majority of referrals in a tertiary care centre as it stands one of the major causes of maternal and perinatal morbidity and mortality. The objective of this study was to study the maternal and fetal outcome in patients with severe pre-eclampsia and eclampsia in a tertiary centre over a period of one year. Methods: Total 150 women with severe eclampsia and eclampsia after 20 weeks of gestation were included. Women with medical complications like anemia, preexisting hypertension, epilepsy, diabetes, vascular or renal disease, multiple gestation, polyhydramnios were excluded. Patients were managed as per existing protocol after proper history, examination and investigations. Anti-hypertensive of choice was alphamethyl-dopa, labetalol and oral nefidipene. Magnesium sulphate was used as anti convulsant. Results: Out of 150 cases of severe pre-eclampsia and eclampsia, majority (69%) were between 20-30 years of age and 47% were primigravida. We had 75 patients with convulsions on admission and 75 with severe pre-eclampsia of whom 11 had convulsions. Headache was most common complaint. Common mode of delivery was caesarean section in 72 (48%) women, majority in view of failed induction or non-progress. Maternal complications were noted in 59% attributed to renal dysfunction, postpartum hemorrhage, DIC, placental abruption, HELLP, pulmonary edema, pulmonary embolism and renal failure. 4 maternal deaths were recorded. Conclusions: Maternal and perinatal complications are more in patients with eclampsia. The incidence of eclampsia can be reduced by better antenatal care, early recognition and prompt treatment of severe pre-eclampsia.